Pseudomonas syringae Pathovar syringae Infection Reveals Different Defense Mechanisms in Two Sweet Cherry Cultivars - Carreras, Claudia (2024)
Pseudomonas syringae pv. syringae is the main causal agent of bacterial canker in sweet cherry in Chile, causing significant economic losses. Cultivars exhibit diverse susceptibility in the field and the molecular mechanisms underlying the differential responses remain unclear. RNA-seq analysis was performed to characterize the transcriptomic response in cultivars Santina and Bing (less and more susceptible to P. syringae pv. syringae, respectively) after 1 and 7 days post-inoculation (dpi) with the bacterium. Symptoms of bacterial canker became evident from the fifth day. At 1 dpi, cultivar Santina showed a faster response to infection and a larger number of differentially expressed genes (DEGs) than cultivar Bing. At 7 dpi, cultivar Bing almost doubled its DEGs, while cultivar Santina tended to the normal DEG levels. P. syringae pv. syringae infection downregulated the expressions of key genes of the photosynthesis process at 1 dpi in the less susceptible cultivar. The results suggest that the difference in susceptibility to P. syringae pv. syringae is linked to the timeliness of pathogen recognition, limiting the bacteria’s dispersion through modeling its cell wall, and regulation of genes encoding photosynthesis pathway. Through this study, it has been possible to progress the knowledge of relevant factors related to the susceptibility of the two studied cherry cultivars to P. syringae pv. syringae.